Overlap between bowhead whales (Balaena mysticetus) and vessel traffic in the North American Arctic and implications for conservation and management. (December 2022) - Halliday, William D.; Le Baron, Nicole; Citta, John J.; Dawson, Jackie; Doniol-Valcroze, Thomas; Ferguson, Megan; Ferguson, Steven H.; Fortune, Sarah; Harwood, Lois A.; Heide-Jørgensen, Mads Peter; Lea, Ellen V.; Quakenbush, Lori; et al.
Abstract: Collisions between vehicles and wildlife is a global conservation concern, and vessel strikes are a leading cause of serious injury and mortality for baleen whales. Yet vessel strikes have rarely been studied in the Arctic. Vessel traffic is increasing throughout the Arctic as sea ice is declining, leading to increased overlap between vessels and whales. We examined hypothetical vessel strike risk for the Bering-Chukchi-Beaufort (BCB) and Eastern Canada-West Greenland (ECWG) populations of bowhead whales during the open-water shipping season. We used satellite telemetry and aerial survey data to calculate monthly relative density of both populations, and satellite vessel tracking data to calculate monthly vessel density and speed. We estimated vessel strike risk by multiplying whale density by vessel density corrected by vessel speed. For the BCB population, the highest relative risk was near Utqiaġvik and Prudhoe Bay, Alaska, USA, and near Tuktoyaktuk, Northwest Territories, Canada. For the ECWG population, the highest risk was in the Gulf of Boothia, Cumberland Sound, and near Isabella Bay, Nunavut, Canada. Strike risk was highest in August and September, corresponding with monthly trends in vessel traffic. This study provides important information for focussed monitoring and to minimize/mitigate the threat of vessel strikes to bowhead whales. Although vessel strike risk is presently lower for these populations than for other temperate large cetacean populations, bowhead whale behaviour and projected increases in traffic elevates their risk in the Arctic. Measures to mitigate vessel strike risk to bowhead whales will likely benefit other Arctic marine mammals like beluga and narwhal.